Keratins Regulate p38MAPK-Dependent Desmoglein Binding Properties in Pemphigus - Vielmuth, Franziska; Walter, Elias; Fuchs, Michael; Radeva, Mariya Y.; Buechau, Fanny; Magin, Thomas M.; Spindler, Volker; Waschke, Jens (Frontiers in Immunology, 2018)
Keratins are crucial for the anchorage of desmosomes. Severe alterations of keratin organization and detachment of filaments from the desmosomal plaque occur in the autoimmune dermatoses pemphigus vulgaris (PV) and pemphigus foliaceus (PF) which are mainly caused by autoantibodies against desmoglein (Dsg) 1 and 3. Keratin alterations are a structural hallmark in pemphigus pathogenesis and correlate with loss of intercellular adhesion. However, the significance for autoantibody-induced loss of intercellular adhesion is largely unknown. In wt murine keratinocytes, pemphigus autoantibodies induced keratin filament retraction. Under the same conditions, we used murine keratinocytes lacking all keratin filaments (KtyII k.o.) as a model system to dissect the role of keratins in pemphigus. KtyII k.o. cells show compromised intercellular adhesion without antibody treatment which was not impaired further by pathogenic pemphigus autoantibodies. Nevertheless, direct activation of p38MAPK via anisomycin further decreased intercellular adhesion indicating that cell cohesion was not completely abrogated in the absence of keratins. Direct inhibition of Dsg3, but not of Dsg1, interaction via pathogenic autoantibodies as revealed by atomic force microscopy (AFM) was detectable in both cell lines demonstrating that keratins are not required for this phenomenon. However, PF-IgG shifted Dsg1 binding events from cell borders towards the free cell surface in wt cells. This led to a distribution pattern of Dsg1 binding events similar to KtyII k.o. cells under resting conditions. In keratin-deficient keratinocytes PF-IgG impaired Dsg1 binding strength, which was not different from wild-type (wt) cells under resting conditions. In addition, pathogenic autoantibodies were capable of activating p38MAPK in both, KtyII wt and k.o. cells, the latter of which already displayed robust p38MAPK activation under resting conditions. Since inhibition of p38MAPK blocked autoantibody-induced loss of intercellular adhesion in wt cells and restored baseline cell cohesion in keratin-deficient cells, we conclude that p38MAPK signaling is i) critical for regulation of cell adhesion ii) regulated by keratins and iii) targets both keratin-dependent and -independent mechanisms.